Influence of gamma radiation on optical constants and optical energy gap of ZnO thin films (Journal of the College of Basic Education, 2023)
We have studied the effect of gamma irradiation on the absorption spectra and the optical energy gap of ZnO thin films. The optical transmission (T%) in the wavelength range 300-900 nm of film deposited at 200 °C on glass substrate was measured. The dependence of the absorption coefficient (α) on photon energy was determined as a function of gamma irradiation. The films show direct allowed interband transition that influenced by the gamma irradiation. Optical constants like refractive index, extinction coefficient and dielectric constants (εr),( εi) increased after irradiation. The results can be discussed on the basis of γ-irradiation-induced defects in the film.